CORRUPTION, GOVERNMENT SPENDING AND ECONOMIC GROWTH IN SELECTED ECOWAS COUNTRIES - M. A Dada; A. O Adedeji; O. A Fatola (Malete Journal of Accounting and Finance, 2020)
This study investigated the impact of corruption and government spending on the growth of economies in selected ECOWAS countries using dynamic panel econometric procedures. Data covering 2005-2018 was sourced from World Development Indicator (WDI) and Transparency International and subjected to panel unit root tests and Panel Auto-Regressive Distributed Lag (PARDL) estimations. Findings reveal a positive but insignificant effect of corruption on the growth of the economies in the short run, while in the long run the impact is negative and statistically significant. Also, government spending and gross capital formation positively contributed to the growth of the economies in the long run but the effect of openness to international trade is negative. This study recommends that the governments of ECOWAS countries should holistically tackle corruption and re-orientate citizens on the societal value of hard work and integrity as against getting wealth at all cost, especially through public service. Also, the judiciary system should genuinely promote equity and justice without partiality. Also, expansionary fiscal policy should be engaged especially in the time of recession. The governments in ECOWAS countries should focus on capital projects and investments. Funds should be channelled towards improving infrastructure, creating employment opportunities through empowerment programmes, while openness to trade among ECOWAS countries should be treated with caution